Sistem Pendataan SP2D Pada Dinas Pengelola Keuangan Dan Aset Daerah Kota Lhokseumawe - Miftahul Jannah (Jurnal Sistem Informasi dan Teknologi Jaringan (SISFOTEKJAR), 2021)
The SP2D data collection information system at the Lhokseumawe City DPKAD Office will store all file criteria submitted by each SKPD into the database. This information system will replace the position of a book that used to be an important part of the Treasury, especially the DPKAD Office Salary because SP2D data collection in this field is still using the Manual System. Given the many problems that often arise in this case, then with the system designed, it is hoped that all problems can be overcome. The form of the problem that exists is the loss of a book that stores all files that have been recorded by employees of the Salary treasury department when processing the disbursement of Lhokseumawe city funds. From the various forms of problems that occur, therefore the application of this system is very much needed in the Salary treasury environment. This information system is capable of storing, editing, and deleting data from various files submitted by the SKPD without having to process it manually. So that this information system can help reduce the workload in the Salary treasury field and increase the efficiency of employee performance.